DEEP TIME, FAST THREADS: NEO-FOLK ART AND PLATFORM TEMPORALITY IN GUIZHOU - FUNA, YE (AoIR Selected Papers of Internet Research, 2026)
The advent of short video platforms in China has heralded a new chapter for Neo-folk art—a contemporary aesthetic that melds folk utopia, pop culture, and propaganda. This paper explores Neo-folk art as a self-sustained system within the digital age, where it thrives independently thanks to the internet's pervasive influence. Neo-folk art remains a testament to the creative spirit originating from everyday life and transcending it.This paper argues that the proliferation of short videos has brought rural and urban cultures into the wild limelight, showcasing a raw and untamed creativity. Traditional folk customs, beliefs, and arts, once confined to specific localities, are now experiencing a form of dissemination and transformation that molds them to fit new media formats. With examples ranging from Fujian's "You Shen" rituals evolving new deities, this study highlights the metamorphosis of folk artistry.Moreover, local cultural and tourism bureaus have begun to adapt content for short video dissemination, emphasizing the adaptability of folk expressions to modern-day communication channels. However, internet-born subcultures like "Smart （Sha Ma Te）" confront the dichotomy of being both celebrated and regulated, revealing the complexities of the digital realm.This study seeks to delineate how Neo-folk art, through the medium of short videos, represents a dynamic intersection of traditional ethos and digital modernity, crafting a new narrative for Chinese folk culture in the global artistic and social landscape.